KESEHATAN HUTAN DI BLOK KOLEKSI TUMBUHAN DAN/ATAU SATWA TAHURA WAN ABDUL RACHMAN PROVINSI LAMPUNG - Dina Pertiwi; Rahmat Safe’i; Hari Kaskoyo; Rahmat Safei (Jurnal Hutan Tropis, 2020)
The research has been conducted in the forest area block collection of plants and/or animals Wan Abdul Rachman Forest Park Lampung Province, which is in Sumber Agung Subdistrict, Kemiling Subdistrict, Bandar Lampung city covering 141.18 ha. The study was conducted to obtain forest health status at the study site. The data collection method uses the forest health monitoring (FHM) technique on 8 cluster clusters with a sampling intensity of 2.30%. The results showed that 25% (2 clusters) were categorized very well, 38% (3 clusters) were categorized as good, 12% (1 clusters) were categorized as moderate and 25% (2 clusters) were categorized as very poor. There needs to be maintenance activities for trees in the research location so that the functions and benefits of the area can be optimized